CLUSTERING PATTERN OFADOLESCENT RISKY BEHAVIOR: RESEARCH RESULTS ANALYSIS - Rakhimkulova, Anastasiya (PSYCHOLOGICAL JOURNAL, 2017)
Negative outcomes of risky behavior involvement influence multiple spheres of adolescent lives. When a teenager takes on several types of risky behavior at the same time, or in other words, when his or her risky behavior clusters, the adolescent becomes subject to even harsher unfavorable impacts. We believe that trying out some risky behavior can start as typical teenage experimenting with the environment and self. However, nailing down on risky behavior and especially its clustering can only be possible if determined by some specific psychological complex within adolescent personality structure. The article presents results of the study of risky behavior prevalence and psychological specifications of Ukrainian teenage schoolchildren of 12-18 years of age. The focus of the study spots types of risky behavior associated with possible negative outcomes for teenage health and life: substance abuse, unhealthy sexual behavior, violence, extreme sports, internet addiction. Though there is a number of studies of multiple risky behaviors, we failed to find ones that would examine the patterns of risky behavior clustering. For each type of risky behavior – substance abuse, extreme risky behavior, food disorders, unhealthy sexual behavior, violence and self-harming behavior – the data is provided on how it clusters with other risky behaviors and psychological features of adolescents. Almost all types of risky behavior were found to cluster with self-harming and suicidal behavior. The article renders results of the cluster analysis, which allowed us to compose a hypothesis of how risky behaviors actually get clustered during adolescence. According to data obtained we believe that risky behavior involvement is provoked by certain psychological states caused by facing violence during childhood and early adulthood. As a result, the psychosexual development follows a disharmonic pattern and the susceptibility to early substance abuse is created. Whether the violence faced was real (physical or sexual), or virtual (when communicating in the Internet), it led to settling emotional instability and lack of will-power. The suffered trauma anchors primitive and unproductive coping strategies, making and adolescent vulnerable to stressful life events. Adolescent’s self-attitude is also tampered. Life dissatisfaction, inability to adapt within the community, negative future perception – are just a few negative aspects that override adolescents with risky behavior.